Forever and a duke - Burrowes, Grace; Bowen, Kelly (Romance fiction writer) (Burrowes, Grace. Rogues to riches novel., 2019)
Wrexham, Duke of Elsmore, is overrun by family obligations. With three sisters to escort about Town, a legion of cousins to look after, and aunties who insist he dance with every eligible young woman, he barely has time to manage his dukedom. When he finally carves out a moment to evaluate his family's finances, he learns that he -- and his sisters -- are on the verge of social catastrophe. Eleanora Hatfield has an uncanny knack for numbers, but she knows from experience that dealing with the peerage can only lead to problems. Though she wants nothing to do with any titled gentleman, she reluctantly agrees to help when Rex seeks aid from her employer. What starts out as an unwanted assignment soon leads to forbidden kisses and impossible longings. But with scandal haunting Ellie's past and looming in Rex's future, how can true love lead to anything but heartbreak? Includes the bonus story "The Lady in Red" by Kelly Bowen!